Examining Students’ Perceptions of Equity in Informal STEM Education: A Community-Engaged, Visual Method - Peralta, Karie Jo; Mann, Sloan Eberly (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2025)
This report from the field presents a community-engaged, visual method for evaluating students’ perceptions of equity in Maker Club, an informal STEM (Science, Technology, Math, and Engineering) education program in Ohio. The purpose of the program is to increase access to and interest in STEM fields among underserved communities. A total of fifteen middle school-aged program participants from two cohorts that were hosted at two different after-school program sites engaged in participant-employed photography to document their views of the implementation of six design principles for equitable learning. The evaluation process unfolded in five phases: 1) recruitment of co-researchers, including explanation of guidelines; 2) teaching co-researchers how to use the camera, including testing out the camera; 3) co-researchers observing, and taking pictures of, students and staff engaged in the makerspace; 4) informal photo interviewing; 5) sharing with program staff via informal conversations and a formal meeting discussion. Takeaways include that co-researchers perceived students benefiting from social support, community partner presence, and local knowledge being recognized. Lessons learned entail keeping students on track, ensuring that there is enough staff support focused on the evaluation process, and being open to other potential, meaningful uses of co-researchers’ photos.